Urgensi Pendidikan Inklusif: Studi Kasus Pada Kegiatan "B' Religi" di SMA Negeri 3 Kota Malang - Faridi, Faridi (J-PAI: Jurnal Pendidikan Agama Islam, 2020)
This article wants to examine the importance of inclusive education for students in SMA Negeri 3 Malang. Through one of its religious activities entitled B’Religi, this school wants to teach its students about tolerance and respect for different groups. This is based on the plurality of the Indonesian nation. This research uses a qualitative approach with a single case study type. Data collection techniques are carried out through observation, interviews and documentation. Meanwhile, data analysis used a descriptive-exploratory model involving three components of analysis, namely: data reduction, data presentation, and conclusion drawing. This research paper concludes that the application of inclusive education cannot be done only in a conceptual level, namely formal learning in the classroom. Inculcating an inclusive attitude which means respecting different religious groups, for example, because in SMA 3 Malang there are several students from various religions, it is very important to be nurtured through refraction and modeling.